A New Algorithm for Designing the Parameter of Damped-Type Double Tuned Filter - Haposan Yoga Pradika Napitupulu; Chairul Gagarin Irianto (IAES Indonesia Section, 2018)
Due to harmonics problems generated by converter devices. Currently, passive filter has been widely used in suppressing harmonics distortion. Passive filter which mostly used is double tuned filter. However, double tuned filter doesn't have a damping resistor which can prevent network elements from exposing to harsh condition such as when the system reactance and the filter impedance are conjugated, this condition can cause severe overvoltage harmonics on the filter and other power system components. There is a new configuration of double tuned filter that has damping resistor, called damped-type double tuned filter. Aiming at the question of parameter of damped-type double tuned filter, a new algorithm for designing the parameter of damped-type double tuned filter is proposed based on the relationship between impedance of two single tuned filter and one double tuned filter, and also based on the resonance at tuned frequency one and tuned frequency two are close to zero. Simulation result from MATLAB shows that the impedance of damped-type double tuned filter designed with this algorithm is appropriate. In addition, the simulation result from PSIM shows that damped-type double tuned filter designed with this algorithm works well.